Sacubitril/valsartan reduces indications for arrhythmic primary prevention in heart failure with reduced ejection fraction: insights from DISCOVER-ARNI, a multicenter Italian register. Issue 1 (21st December 2021) - Pastore, Maria Concetta; Mandoli, Giulia Elena; Giannoni, Alberto; Benfari, Giovanni; Dini, Frank Lloyd; Pugliese, Nicola Riccardo; Taddei, Claudia; Correale, Michele; Brunetti, Natale Daniele; Carluccio, Erberto; Mengoni, Anna; Guaricci, Andrea Igoren; et al.
Abstract: Aims: This sub-study deriving from a multicentre Italian register [Deformation Imaging by Strain in Chronic Heart Failure Over Sacubitril-Valsartan: A Multicenter Echocardiographic Registry (DISCOVER)-ARNI] investigated whether sacubitril/valsartan in addition to optimal medical therapy (OMT) could reduce the rate of implantable cardioverter-defibrillator (ICD) indications for primary prevention in heart failure with reduced ejection fraction (HFrEF) according to European guidelines indications, and its potential predictors. Methods and results: In this observational study, consecutive patients with HFrEF eligible for sacubitril/valsartan from 13 Italian centres were included. Lack of follow-up or speckle tracking data represented exclusion criteria. Demographic, clinical, biochemical, and echocardiographic data were collected at baseline and after 6 months from sacubitril/valsartan initiation. Of 351 patients, 225 (64%) were ICD carriers and 126 (36%) were not ICD carriers (of whom 13 had no indication) at baseline. After 6 months of sacubitril/valsartan, among 113 non-ICD carriers despite having baseline left ventricular (LV) ejection fraction (EF) ≤ 35% and New York Heart Association (NYHA) class = II–III, 69 (60%) did not show ICD indications; 44 (40%) still fulfilled ICD criteria. Age, atrial fibrillation, mitral regurgitation > moderate, left atrial volume index (LAVi), and LV global longitudinal strain (GLS) significantly varied between the groups. With receiver operating characteristic curves, age ≥ 75 years, LAVi ≥ 42 mL/m 2 and LV GLS ≥−8.3% were associated with ICD indications persistence (area under the curve = 0.65, 0.68, 0.68, respectively). With univariate and multivariate analysis, only LV GLS emerged as significant predictor of ICD indications at follow-up in different predictive models. Conclusions: Sacubitril/valsartan may provide early improvement of NYHA class and LVEF, reducing the possible number of implanted ICD for primary prevention in HFrEF. Baseline reduced LV GLS was a strong marker of ICD indication despite OMT. Early therapy with sacubitril/valsartan may save infective/haemorrhagic risks and unnecessary costs deriving from ICDs. Graphical Abstract: